2016
DOI: 10.1038/mt.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Morpholino-mediated Knockdown of DUX4 Toward Facioscapulohumeral Muscular Dystrophy Therapeutics

Abstract: Derepression of DUX4 in skeletal muscle has emerged as a likely cause of pathology in facioscapulohumeral muscular dystrophy (FSHD). Here we report on the use of antisense phosphorodiamidate morpholino oligonucleotides to suppress DUX4 expression and function in FSHD myotubes and xenografts. The most effective was phosphorodiamidate morpholino oligonucleotide FM10, which targets the polyadenylation signal of DUX4. FM10 had no significant cell toxicity, and RNA-seq analyses of FSHD and control myotubes revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 36 publications
1
103
0
3
Order By: Relevance
“…This RNA-seq study indicated that 96% of the genes upregulated in FSHD myotubes were at least partly reduced by the PAS-PMO, while 89% of the mRNAs that were significantly reduced had a least some upregulation in FSHD myotubes. The inhibition was dose-dependent with 50% reduction of footprint gene expression in the 1–3 µmol/L PMO concentration range [74]. The inhibition was also obtained in a model of FSHD muscle xenograft in an immunosuppressed mouse with electroporation-mediated PMO administration [74].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This RNA-seq study indicated that 96% of the genes upregulated in FSHD myotubes were at least partly reduced by the PAS-PMO, while 89% of the mRNAs that were significantly reduced had a least some upregulation in FSHD myotubes. The inhibition was dose-dependent with 50% reduction of footprint gene expression in the 1–3 µmol/L PMO concentration range [74]. The inhibition was also obtained in a model of FSHD muscle xenograft in an immunosuppressed mouse with electroporation-mediated PMO administration [74].…”
Section: Resultsmentioning
confidence: 96%
“…The inhibition was dose-dependent with 50% reduction of footprint gene expression in the 1–3 µmol/L PMO concentration range [74]. The inhibition was also obtained in a model of FSHD muscle xenograft in an immunosuppressed mouse with electroporation-mediated PMO administration [74]. …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…DUX4 est donc une cible de choix pour les différentes approches thérapeutiques de la DMFSH. Dans cette étude [1], l'analyse RNASeq de cellules de patients et de contrôles familiaux a permis l'identification de cibles transcriptionnelles directes et indirectes de DUX4, servant ultérieurement de biomarqueurs de l'activité de DUX4, car la mesure directe des mRNA de DUX4 et de la protéine est plus déli-cate et aléatoire du fait de la présence de nombreux homologues. Plusieurs oligonucléotides antisens basés sur la chimie des phosphorodiamidates de morpholinos (PMOs) ont été testés pour leur efficacité d'inhibition in vitro, en cultures de myotubes.…”
Section: Jean-thomas Vilquinunclassified